Effect of surface modified magnesium sulfate whisker on crystallization and mechanical properties of polybutylene succinate composites. Issue 9 (15th July 2022) - Hou, Hongbo; Pu, Zejun; Zhu, Rongli; Wang, Xu; Li, Xianyong; Yu, Dayang; Wu, Fang; Zhong, Jiachun
Abstract: In this study, the M@MgSO4 whiskers (MOSw) are successfully prepared by the surface treatment of MOSw. Then, using polybutylene succinate (PBS) as the matrix and M@MOSw as the filler, the PBS/M@MOSw and PBS/MOSw composite films were prepared. The Fourier transform infrared spectroscopy and scanning electron microscopy results show that the PBS was successfully coated on the surface of MOSw. With the introduction of the M@MOSw, it has been improved the MOSw and the PBS dispersibility and interface compatibility obviously. After the addition of the M@MOSw or MOSw in the PBS‐based composites, not only does the crystallization rate improve, but also the crystal size and structure changes. The PBS/M@MOSw composites show excellent mechanical properties. When the with 10 wt% M@MOSw loading, the tensile strength of the PBS/M@MOSw composites is 34.67 MPa, which is 9.3% higher than that of pure PBS. Meanwhile, when the M@MOSw with 20 wt% loading, the bending strength of PBS/M@MOSw increases significantly, reaching 45.26 MPa, which is improved 35.55% than that of pure PBS. Abstract :